A question about an education and peace in the thought of Gabriel Marcel - Marta Krupska (Jan Dlugosz University, 2022)
The main consideration of this analysis focuses on personalistic and existential thinking of Gabriel Marcel concerning the philosophical and ethical importance of peace. The aim of research is to present the inspiration from Gabriel Marcel's thought for pedagogical reflection mutual relation between peace and education. The main research problem is analysis of the importance of the issue of peace that is present in the philosophy of Gabriel Marcel for reflection on personal development and education. The reflection process was conducted on the basis of an content analysis based in particular on Gabriel Marcel's speech delivered on the occasion of the award Prix de la Pax granted by Union des Libraires allemands in 1964. The results of the analysis show that the source of peace is a genuine community between people. This spirit of community is manifested when each person finds in other person real existential qualities and values, when each person considers to be a value for the meaningfulness of its own being. We need an awareness of one's own insufficience and a sense of humility makes real the role of the other for the self so that through interrelationship and intersubjectivity persons in actual situations promote availability and openness toward each other.